INCREASING KNOWLEDGE OF COFFEE FARMERS IN THE COOPERATIVE “KETAKASI” ABOUT USE SMART ECO ROASTING MACHINE THROUGH TRAINING - Dina Rizkina, Fitriana; Abidin, Asroful; Martha Muliasari, Risa; Zainur Ridlo, Muhammad (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Roasted coffee is an Indonesian export product and the Ketakasi Cooperative is one of the coffee exporters and a tourist destination. In its development, the Ketakasi Cooperative needs a machine that can facilitate the roasting process and has a small capacity for profiling and educational tourism. The solution offered is the use of a Smart Eco Roasting Machine. The method for implementing this service is competency development in the form of training and mentoring at the Ketakasi Cooperative which includes three stages of activities, namely the preparation stage, implementation stage, and evaluation stage. Based on the overall evaluation results, there was an increase in the understanding of coffee farmers and cooperative administrators about the roasting process. Training participants are interested in using the Smart Eco Roasting Machine.